Nuclear Magnetic Resonance-Based Metabolomic Analysis Reveals Physiological Stage, Breed, and Diet Effects on the Intramuscular Metabolism of Amino Acids and Related Nutrients in Pigs - Liu, Yingying; He, Qinghua; Azad, Md. Abul Kalam; Xiao, Yi; Yin, Yulong; Kong, Xiangfeng (Frontiers in Veterinary Science, 2021)
Skeletal muscle is a complex tissue that exhibits considerable plasticity in response to nutrients, animal, or its growth stage, but the underlying mechanisms are largely unknown. This study was conducted to evaluate the effects of physiological stage, breed, and diet on the metabolome of the skeletal muscle of pigs. Ninety-six barrows, including 48 purebred Bama mini-pigs, representing the fat type, and 48 Landrace pigs, representing the lean type, were randomly assigned to either a low- or adequate-protein diet (n = 24 per group). The experimental period commenced at five weeks of age and extended to the finishing period. Psoas major muscles (PMM) were collected at the nursery, growing, and finishing stages and the contents of amino acids (AAs), fatty acids (FAs), and metabolites were analyzed using a nuclear magnetic resonance-based approach. Results showed that the most AAs and monounsaturated FAs (MUFA, including C16:1 and C18:1) contents were increased (P < 0.05) gradually, while those of polyunsaturated FAs (including C18:2, C20:4n-6, C20:5n-3, and C22:6n-3) were decreased (P < 0.05) in the PMM with increasing age. Compared to Landrace pigs, Bama mini-pigs had higher (P < 0.05) contents of flavor-related AAs (including methionine, phenylalanine, tyrosine, leucine, and serine) in the nursery and growing stages, and higher (P < 0.05) percentages of saturated FAs and MUFA throughout the trial. Dietary protein levels affected the muscular profiles of AAs and FAs in an age-dependent manner. In addition, the adequate-protein diet increased (P < 0.05) the muscular contents of α-ketoglutarate in the two breeds. These findings indicate that the dynamic profiles of AAs, FAs, and metabolites in pig muscle tissues are regulated by breed, diet, and physiological stage.